Strategi Pengembangan Usaha Budidaya Pembesaran Ikan Patin (Pangasius sp.) di Kecamatan Gandus Kota Palembang - Dwi Elgha Sushanty; Fauziah Fauziah; Dwi Putro Priadi (Jurnal FishtecH, 2017)
Catfish (Pangasius sp.) aquaculture in Gandus district until now have some problems such as decreasing environmental quality due to decreased water quality so resulting water pollution, limited knowledge and skill of cultivators, the technology used is still limited and simple, and technical production has not same of SOP (Standard Operation Procedure) so that production not yet good. Constraints and problems in cultivation need to considered, because in addition to being a challenge also a threats to the development of fish farming. Therefore, catfish aquaculture in Gandus district Gandus subdistrict needs to developed based on application of cultivation technology in accordance with the support environment. The research was held in Gandus district of Palembang. The purposes of this research were to identification enlargement catfish aquaculture situation, analyze internal and external factors of the aquaculture and analyze a developing strategy catfish aquaculture. The research was descriptive. Data resulted were analyzed by descriptive qualitative and quantitative. The score of the IFAS analysis was (-0,18) and score of EFAS was 0,77. The SWOT analysis result was in the third quadran, so the strategy applied is WO strategy (Weakness-Opportunities). WO strategy is a strategy minimalized weakness to get the opportunity. In the business, WO strategy was used in the standard category. Strategy are used water quality management and good in terms of quantity and quality to reduce pollution of the aquatic environment, give training and skills to cultivators about technology utilization and production system to increase global production, the use of appropriate technology to reduce pollution of aquatic environment to increasing market demand, and enhance cultivation cooperation with local agencies in providing extension regarding the implementation of production standards.